2011
DOI: 10.1016/j.ijsolstr.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clustered tensegrity structures using a modified dynamic relaxation algorithm

Abstract: a b s t r a c tTensegrities are spatial, reticulated and lightweight structures that are increasingly investigated as structural solutions for active and deployable structures. Tensegrity systems are composed only of axially loaded elements and this provides opportunities for actuation and deployment through changing element lengths. In cable-based actuation strategies, the deficiency of having to control too many cable elements can be overcome by connecting several cables. However, clustering active cables si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(53 citation statements)
references
References 48 publications
0
50
0
2
Order By: Relevance
“…Rhode-Barbarigos et al (2012b) then studied several deployment methods and showed that utilizing springs, inspired from (Schenk et al 2007), and clustered-cables reduces the number of actuators required for controlled deployment. Bel Hadj Ali et al (2011) proposed an analysis method for clustered tensegrity structures through a modified dynamic relaxation algorithm. Clustered cable elements run continuously through nodes.…”
Section: The Tensegrity Ring Footbridgementioning
confidence: 99%
See 1 more Smart Citation
“…Rhode-Barbarigos et al (2012b) then studied several deployment methods and showed that utilizing springs, inspired from (Schenk et al 2007), and clustered-cables reduces the number of actuators required for controlled deployment. Bel Hadj Ali et al (2011) proposed an analysis method for clustered tensegrity structures through a modified dynamic relaxation algorithm. Clustered cable elements run continuously through nodes.…”
Section: The Tensegrity Ring Footbridgementioning
confidence: 99%
“…A detailed presentation of the modified DR method can be found in (Bel Hadj Ali et al 2011). The numerical model does not include the dimensions of joints and consequently, there are modelling challenges associated with eccentricity, friction and the effect of strut contact on deployment.…”
Section: Numerical Analysismentioning
confidence: 99%
“…El autor querría agradecer la desinteresada y generosa colaboración de Julien Aversen y Landolf Rhode-Barbarigos, poniendo a disposición para esta investigación herramientas de gran utilidad para el análisis de las estructuras aquí expuestas, como son respectivamente el ToyGL (84) y el algoritmo de relajación dinámica modificada (83).…”
Section: Agradecimientosunclassified
“…Structural analyses for various load combinations were performed using dynamic relaxation [36]. Analysis results were used to check safety and serviceability requirements.…”
Section: Tensegrity Bridgementioning
confidence: 99%
“…Moored and BartSmith investigated actuation on a simple tensegrity beam with groups of individual active cable elements that are combined into continuous cables. Bel Hadj Ali et al [36] proposed a modified dynamic relaxation algorithm for static analysis of tensegrity structures including continuous cables. Apart from the numerical example presented in [36,37], no study addressing structural control employing continuous cables for large tensegrity structures is available in the literature.…”
Section: Introductionmentioning
confidence: 99%